Lack of Good Governance and the Generation of Political Crises in Developing Countries: Practical Case of Macedonia, Last Three Years’ Experience (European Journal of Interdisciplinary Studies, 2018)
Having in mind that the political approach and the way of governing today in developing countries is one of the key problems that face, or exists in Macedonia's practice, especially in a country like this, where today, still in these new, political, economic and global conditions and circumstances, we encounter great difficulties in the state of government and the lack of proper functioning of the transparent and principled form of institutions providing public services or those who have a tendency to public service delivery. The main purpose of this paper is to give some clarification about an experience that is often repeated in the practice of developing countries. This paper will raise these problems and issues: What are the underlying reasons for the lack of governance in developing countries?; What steps should be taken by governments of these countries in sense of being more prepared in the process of integrating countries into European structures and how can they prevent crises in the process of political reform? The paper will raise the research aspect by giving the opportunity to recognize the political reasons for the experiences that this country shares in the process that is ongoing even these days. And the last part of this research will focus on the recommendations that will be given to developing countries.